Efektivitas Peran Arbitrase Syariah dalam Menyelesaikan Sengketa Bisnis Syariah - Nurul Fitriyah; Riqqa Soviana (Universitas Muhammadiyah Makassar, 2021)
Sharia arbitration is an institution that plays a role in resolving sharia disputes peacefully outside the general court. Arbitration is regulated in Law no. 30 of 1999 states that arbitration has the right to resolve problems related to civil law. Covers economic, business, financial, trade and industrial issues that apply sharia principles. The purpose of writing this article to know the effectiveness of the role of sharia arbitration in resolving sharia business disputes in Indonesia. Because the process of solving business problems can use litigation (judicial) or non-litigation (outside court). This research focuses on the Shariah Arbitration Instirtuation. The research method uses descriptive qualitative with a normative and juridical approach. Sharia arbitration in Indonesia is considered quite effective in resolving sharia business disputes. Because the disputing parties are more dominant in choosing sharia arbitration than the judicial route, this is due to the fact that sharia arbitration is more flexible in proposing conditions to resolve disputes, more cost and time efficient and prioritizes peace. In addition, the legal basis used by the sharia arbitration institution is in accordance with the Qur'an, hadith and also the MUI Fatwa.